Microbiology and Biotechnology - Lowrie, Pauline; Wells, Susan, 1950- (Cambridge : Cambridge University Press, 1994)
'Microbiology and Biotechnology' is part of the 'Cambridge Modular Sciences' series for A and AS level.
Keywords: Microbiology; Biotechnology